Comparative Genomics of Smut Pathogens: Insights From Orphans and Positively Selected Genes Into Host Specialization - Benevenuto, Juliana; Teixeira-Silva, Natalia S.; Kuramae, Eiko E.; Croll, Daniel; Monteiro-Vitorello, Claudia B. (Frontiers in Microbiology, 2018)
Host specialization is a key evolutionary process for the diversification and emergence of new pathogens. However, the molecular determinants of host range are poorly understood. Smut fungi are biotrophic pathogens that have distinct and narrow host ranges based on largely unknown genetic determinants. Hence, we aimed to expand comparative genomics analyses of smut fungi by including more species infecting different hosts and to define orphans and positively selected genes to gain further insights into the genetics basis of host specialization. We analyzed nine lineages of smut fungi isolated from eight crop and non-crop hosts: maize, barley, sugarcane, wheat, oats, Zizania latifolia (Manchurian rice), Echinocloa colona (a wild grass), and Persicaria sp. (a wild dicot plant). We assembled two new genomes: Ustilago hordei (strain Uhor01) isolated from oats and Ustilago tritici (strain CBS 119.19) isolated from wheat. The smut genomes were of small sizes, ranging from 18.38 to 24.63 Mb. U. hordei species experienced genome expansions due to the proliferation of transposable elements and the amount of these elements varied among the two strains. Phylogenetic analysis confirmed that Ustilago is not a monophyletic genus and, furthermore, detected misclassification of the U. tritici specimen. The comparison between smut pathogens of crop and non-crop hosts did not reveal distinct signatures, suggesting that host domestication did not play a dominant role in shaping the evolution of smuts. We found that host specialization in smut fungi likely has a complex genetic basis: different functional categories were enriched in orphans and lineage-specific selected genes. The diversification and gain/loss of effector genes are probably the most important determinants of host specificity.